PHYSIOLOGICAL AND HAEMATOLOGICAL PROFILE OF MALE PURNATHADI BUFFALO CALVES DURING SUMMER - Dhenge, SA; Puralkar, Prajakta; Nagre, SM (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The present study was carried out to determine growth, physiological and haematological profiles of growing male Purnathadi buffalo calves during summer. The determined profile values were within the normal range for buffalo except increased respiration rate and growth profile values were lower in summer and as compared with the previous reports, growth of male Purnathadi buffalo calves was impaired very severely